Incidence Analysis of an Acute Respiratory Infection due to Climate Conditions and PM10 Concentration in West Jakarta Region - Rini Hidayati; Septina Tri Anggiani; Ikoh Maufikoh (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2017)
Humans have contributed to an increased of particulates concentration due to their daily life activities including from transportation, industry, infrastructure and household. One common particulate found is PM10, which affects human health such as respiratory tract disorders. Weather condition controls PM10 concentration. This research aims to analyze the weather impact on PM10 concentration associated with the occurrence of acute respiratory infections. We analysed relationship between rainfall and PM10 on day to seasonal timescale resolution. Our results show a negative correlation between rainfall and PM10. It appears that season strongly influences the correlation with high and low PM10 concentration occurred during July-August (dry season) and December-February (wet season), respectively. At daily basis, our findings revealed that minimum PM10 concentration occurred at 06.00 am, and it will increase following human activities while people are going to workplace and school. Further, we found that a combining of low humidity and high PM 10 concentration will lead to high acute respiratory infections.